Anti-trafficking saviors: celebrity, slavery, and branded activism - Heynen, Robert (Crime, media, culture, 2022)
This article traces the development of popular forms of anti-trafficking activism in the United States through a social network and discourse analysis that focuses on NGO websites, celebrity advocacy, merchandising, social media campaigns, and policy interventions. This "branded activism," as we describe it, plays an important role in legitimizing an emerging anti-trafficking consensus that increasingly shapes both US foreign policy and domestic policing, and is frequently driven by an anti-sex work politics. Popular anti-trafficking discourses, we find, build on melodramatic narratives of victims and (white) saviors, depoliticize the complex labor and migration issues at stake, reinforce capitalist logics, and enable policy interventions that produce harm for migrants, sex workers, and others ostensibly being "rescued." Celebrity and marketing-driven branded activism relies especially strongly on parallels drawn between histories of chattel slavery and what anti-trafficking campaigns call "modern-day slavery." We challenge these parallels, particularly as they encourage participants to see themselves as abolitionist saviors in ways that reinforce neo-liberal notions of empowerment rooted in communicative capitalist networks.